Circularly polarized microstrip patch antenna array for GPS application - Taher Khalifa; N. M. Sahar; N. Ramli; M. T. Islam (Indonesian Journal of Electrical Engineering and Computer Science, 2019)
The 12 elements antenna array for GPS system having high gain with circular polarization is presented in this paper. The circularly polarized antenna is very suitable for the use of various wireless systems such as Global Positioning System with operating frequency is 1.27 GHz with AR is less than 3 dB between 82˚ and 140˚.The antenna consists of twelve main radiation patches connected in parallel. The antennas array are designed on the Rogers RT5880 substrate with a dielectric constant (εr) of 2.2 and thickness is 0.787 mm. The antenna is excited with an inset feed line and it operates in L-band with a resonant frequency of 1.27 GHz.